Cerebral Vasculitis in Henoch-Schönlein Purpura: A Case Report - Meltem AKÇABOY; Kibriya FİDAN and Yaşar KANDUR and Emel ISIYEL and Bahar BÜYÜKKARAGÖZ and Sevcan Azime BAKKALOĞLU EZGÜ and Necla BUYAN and Enver HASANOĞLU and Oğuz SÖYLEMEZOĞLU (Archives of Rheumatology, 2017)
Henoch-Schönlein purpura is a common form of systemic small vessel vasculitis in childhood. Although headache and behavioral changes have been described in a significant proportion of children with Henoch-Schönlein purpura, severe neurological complications are rare. In this article, we report a case of central vasculitis in a four-year-old boy who presented with hemiplegia and aphasia. The treatment options for cerebral vasculitis of Henoch-Schönlein purpura are numerous but controversial in pediatric patients. Our patient was successfully treated by pulse methylprednisolone and pulse cyclophosphamide. The patient was followed-up for four years without any sequel.